GENDER DIFFERENCES IN MENTAL HEALTH AMONG HIGHER SECONDARY STUDENTS IN IMPHAL WEST DISTRICT, MANIPUR - Soram, Linthoi; Devi, Chongtham Beda (International Journal of Research -GRANTHAALAYAH, 2025)
This study aims to investigate the differences in mental health between male and female higher secondary students and to compare the differences in mental health based on school, home, and peer dimensions. Hypotheses of the study include that there will be no difference in mental health between males and females based on school, home, and peer dimensions. The descriptive survey method is employed. The random sampling technique is used to collect data. 243 higher secondary students (124 males and 119 females) aged 15-19 years from four (4) higher secondary schools in Imphal West District, Manipur were selected for the study. A standardized scale, the “Mental Health Scale,” developed by Dr. Sushma Talesaro and Dr. Akhtar Bano (2017), was administered to the respondents. To analyse the data, percentage, mean, standard deviation, and an independent samples t-test were used. No significant difference between males and females was found in overall mental health, and in the school, home, and peers domains.